WOMEN’S AND MEN’S EMOTIONAL ABILITIES AND STRESS COPING STRATEGIES - Piekarska, Joanna (Studia Psychologica: Theoria et praxis, 2015)
The present study examined the links between two emotional abilities (emotion recognizing and emotion understanding) and coping strategies in men and women. The analysis was conducted on the sample of 228 adults (109 women and 119 men) aged 18–58 years (Mage = 27,46 years). Coping strategies were measured by the COPE inventory and emotional abilities were measured by the Emotional Intelligence Scale – Faces (SIE-T) and the Emotion Understanding Test (TRE). The results indicated gender differences in emotion understanding and some coping strategies. Different correlations between emotional abilities and coping strategies in men and women were also observed. This finding may suggest that emotional abilities play different role in stress coping in men and women.